Pengembangan Media Teka Teki Silang Berbasis Model Teams Games Tournament terhadap Motivasi dan Hasil Belajar IPA Materi Biologi Kelas VII MTs As-Salam Palembang - Yusnia, Yeni; Hidayat, Saleh; Astriani, Meli (BIODIK, 2025)
This study aims to develop TTS media based on the Teams Games Tournament model and to determine the validity, practicality, effectiveness, motivation, and learning outcomes in science material. The method used in this study is the 4D development model (define, design, develop, and disseminate). The product trial was conducted on 25 students in class VII MTs As-Salam Palembang, also involving one science teacher as a respondent for the practicality test. The results showed that after validation by language experts, materials, media, learning devices and teaching materials, it was obtained that the average indicator for language was 78%, material 78%, and media 79% with good and valid qualifications. In learning devices, the average indicator was 94% and teaching materials 84% with very good qualifications and very valid information. The results of the expert assessment of media practicality obtained an average indicator, namely 86% of teachers with valid qualifications and 84% of students with very strong qualifications. Based on the results of the tabulation of student response data on the effectiveness of the biology TTS media, a percentage of 81.16% was obtained with a very high category. Then the value of student responses to learning activities was 88.05 with very good criteria. This study shows that the TTS media based on the Teams Games Tournament model developed has met the criteria of validity, practicality, and effectiveness. High validity indicates that the content and media developed are in accordance with learning standards. High practicality from teachers and students indicates that this media is easy to use and helps in the learning process. Increased motivation and learning outcomes are classified as moderate indicating that the use of this media can have a positive impact on students' understanding of concepts. However, in the future this media can continue to be refined to be able to produce higher improvements. It can be concluded that by using TTS media, students can be motivated in the learning process because they learn while playing.